Geochemistry of siltstones in the North Qilian Zhongbao–Mayinggou formations (Late Ordovician–Early Silurian): implications for paleoclimate, paleoweathering, and tectonic setting - Xia, Yu; Hou, Qian; Mou, Chuanlong (Frontiers in Earth Science, 2024)
The Late Ordovician-Early Silurian period witnessed the Phanerozoic mass extinction, glacial events and volcanic events. Paleoweathering indices (CIA, CIW, and PIA) indicate that the source area weathering changed from week-moderate to intense.CIA values in the upper Zhongbao formation range from 66.71% to 73.97%, indicating a drier and colder climate. Upward the CIA values on the bottom of the Mayinggou Formation returns to the high value quickly (from 73.86% to 81.31%), suggesting that the ice age ended, the climate got warmer and wetter, and the sea level went up. The Al2O3-(CaO*+Na2O)-K2O triangular plots, Hf-La/Th and SiO2-Al2O3/TiO2 bivariate plots infer that the source of the siltstones in the two formations is mostly from the felsic igneous rocks. The samples from the Zhongbao-Mayinggou Formation have similar chondrite-normalized REE patterns to that of the North Qilian volcanic arc rocks. Geochemical discrimination plots displayed that the sediments of the Zhongbao-Mayinggou formation were come from the active continental margin setting.